IMPLEMENTATION OF DIABETES ONE-STOP CENTRE (DOSC) IN A TERTIARY HOSPITAL IN CENTRAL PAHANG, MALAYSIA: SUCCESS, FAILURES AND LIMITATIONS - See, Chee Keong; Chin, Hui Wenn; Maria, Dorothy; Bernard, Anthony; Abu Bakar, Azharni Aysha Semah; Yusoff, Yuhin Asadulhaq; Veerasamy, Hema Lata; Dawi, Suzatul Fadzillah; Arifin, Noorhidayah; Ooi, Xin-Yi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION A comprehensive diabetes management currently focuses on ensuring patient self-management. To achieve this goal, a cohesive management team that includes physicians, diabetes educators, pharmacist, dietician, physiotherapist and podiatrist is required. Implementation of a DOSC provides an ideal avenue for patients to receive a holistic assessment. DOSC was implemented in Hospital Sultan Haji Ahmad Shah, a Malaysian tertiary hospital in central Pahang since 2015. DOSC was an ideal concept for patient assessment since this hospital had wide area of patient coverage. This study aimed to assess the impact of DOSC implementation on diabetes outcomes such as HbA1c control, diabetes complications, mortality and clinic defaulter. METHODOLOGY This is a cross-sectional study assessing patients who were recruited into DOSC between 2015 and 2017. Baseline data and follow-up were collected through patient information system. Information included: demographics, HbA1c, diabetes complications, mortality and 2018 latest follow-up data. RESULTS Five hundred patients were recorded with mean age of 58.7±SD1.49 years and 64% male. The mean HbA1c at recruitment was 9.86±SD1.2%. More than 70% of patients were on insulin therapy. 22.4% had retinopathy, 23.2% had nephropathy and 10.4% had neuropathy. At latest follow-up, there was significant HbA1c reduction compared to initial recruitment (1.23±SD2.7%, p<0.01). There was a 5% mortality and 10% defaulter rates in the 3 years of follow-up. DOSC concept may seem ideal but many barriers were identified impeding its implementation. CONCLUSION Despite better HbA1c control, there are limitations in implementation of DOSC. Sustaining the provision of care requires optimal resources and manpower and maintenance of patient interest in diabetes care.